Degradation capability of Acinetobacter indicus LXX12 on tobacco straw and its whole genome analysis - Xiaoxiao Lu; Huang Ying; Jing Liu; Jianyu Gou; Zhengxiong Zhou; Shishuang Xie (Scientific Reports)
Abstract A high-efficiency tobacco straw-degrading strain, Acinetobacter indicus LXX12, was isolated from tobacco-planting soil in Anshun City, Guizhou Province, China. Systematic investigations were conducted on its physiological and biochemical characteristics, environmental adaptability, and degradation mechanisms. The strain is a Gram-negative, non-motile aerobic bacterium capable of tolerating extreme conditions, including a pH range of 6–11, salinity up to 10%, and temperatures between 15 °C and 44 °C, while exhibiting notable nicotine tolerance. The strain demonstrated robust cellulolytic activity, with a CMCase activity of 65.25 U/mL after 24 h incubation. Inoculation with LXX12 resulted in a 65.7% weight loss of tobacco straw after 35 days of treatment. Scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR) analyses confirmed its synergistic degradation of cellulose, hemicellulose, and lignin. Whole-genome sequencing revealed that the strain’s genome harbors 65 CAZy enzyme genes, including 11 glycoside hydrolases (GH3 and GH5 family endoglucanases and β-glucosidases) for cellulose degradation, 6 auxiliary redox enzymes (AA3, AA4, and AA6 family vanillyl alcohol oxidases and 1,4-benzoquinone reductases) for lignin modification, as well as CE3 acetylxylan esterases and CBM50 substrate-binding modules. These enzymes collectively form a “backbone depolymerization-side chain modification-redox-driven” multi-enzyme synergistic network. KEGG pathway analysis further elucidated its capability to convert lignin derivatives into carbon sources via benzoate degradation, glycolysis, and the tricarboxylic acid (TCA) cycle. Based on 16 S rDNA sequence alignment, the strain showed 99.78% similarity to Acinetobacter indicus CIP 110,367 strain A648, and was designated Acinetobacter indicus LXX12 despite notable phenotypic discrepancies. The isolation and functional characterization of this strain provide a novel microbial resource for lignocellulose bioconversion, combining high efficiency with environmental adaptability, and hold significant potential for agricultural waste valorization.